Algorithms for Calculation of Parameters of Electrochemical Biosensor - Shumyantseva, V.V.; Pronina, V.V. (Biomedical Chemistry: Research and Methods, 2022)
The aim of this work is to present the experimental results in the form of an algorithm for analyzing the modification of screen printed electrodes, including the possibility of its regeneration for irreversibly oxidizing biologically active compounds (drugs, DNA and proteins). A protocol was developed for quantitative analysis and study of the mechanism of drug-DNA interaction by differential pulse voltammetry, including the following parameters: complex binding constant, Gibbs free energy, and electrochemical coefficients of the toxic effect.